Beer production technology - Yurchuk, Lyudmila; Dmitriev, Ilya (My University, 2013)
Beer is one of the oldest and most complex in preparation of drinks. This article gives the information about the latest technologies in brewering.
Keywords: malt; hop; yeast; wort; fermentation; filtration; солод; хміль; дріжджі; сусло; ферментація; фільтрація; кафедра іноземних мов професійного спрямування